Measurement and Physiological Relevance of the Maximal Lipid Oxidation Rate During Exercise (LIPOXmax) - Brun, Jean-Frédéric; Varlet-Marie, Emmanuelle; Romain, Ahmed Jérôme; Mercier, Jacques (IntechOpen, 2012)
None